2020
DOI: 10.31687/saremnms.2020.0.11
|View full text |Cite
|
Sign up to set email alerts
|

Nuevos hallazgos y localidades de Dioctophyme renale (Nematoda, Enoplida, Dioctophymatidae) en Chrysocyon brachyurus (Carnivora: Canidae) para la República Argentina

Abstract: RESUMENDocumentamos 19 nuevos registros de Dioctophyme renale en Chrysocyon brachyurus para Argentina en un período de 15 años. Se localiza geográficamente cada registro, se detallan los métodos de diagnóstico empleados y se describe el contexto epidemiológico en cada caso. Esta información contribuye a ampliar nuestro conocimiento de esta asociación parásito/hospedador.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The species is considered a wild reservoir and definitive host of Dioctophyma renale ; therefore, it is the most reported parasite for the species (Cansi et al, 2012;Di Nucci et al, 2020;González et al, 2013;Natalini et al, 2021;Oliveira et al, 2021), although it was not found in the present case.…”
Section: Copro-parasitologymentioning
confidence: 59%
“…The species is considered a wild reservoir and definitive host of Dioctophyma renale ; therefore, it is the most reported parasite for the species (Cansi et al, 2012;Di Nucci et al, 2020;González et al, 2013;Natalini et al, 2021;Oliveira et al, 2021), although it was not found in the present case.…”
Section: Copro-parasitologymentioning
confidence: 59%